Grounded theory assessment of health needs in rural Mississippi Delta region, USA: Implications for health policy and management - Yalanda M. BARNER; Austine U. ONYIA; Russell L. BENNETT; Manoj SHARMA (Journal of Health and Social Sciences)
Introduction: The Mississippi Delta is the most rural and economically disadvantaged area in the United States. Rural communities face challenges in accessing quality healthcare for chronic illnesses and diseases. Engaging community members in identifying and addressing community health issues that are necessary to address chronic diseases and other structural barriers is vital to assisting the community with needed resources. Therefore, the purpose of this study was to assess the health needs and barriers to services in a rural community, in Mississippi Delta, to improve health outcomes. Methods: The study used a grounded theory qualitative design. A purposive sample of twenty residents participated in either face-to-face semi-structured in-depth interviews (n=5) or focus group discussions with key stakeholders (n=2). Data collection focused on the community’s perceptions of health and the resources available to the community. The data from focus group discussions and interviews were transcribed using thematic analysis. Results: Findings indicated that stakeholders and residents acknowledged many of the same chronic diseases as in the nation, barriers to access to care as being accentuated and governmental policies not being a priority for this region. Participants identified hypertension, diabetes, mental health, and cancer as the most prevalent diseases. Structural barriers included little access to quality foods and a lack of economic development. Affordable healthcare and smoke-free policies were identified as policies that were impacting community health. Discussion: Participants' issues directly aligned with data regarding the health of the rural Mississippi Delta. Strategies to improve health outcomes in rural communities that emerged included: (1) improvement and practice of healthy habits, (2) provision of more healthcare facilities, (3) increase in access to quality of foods, and (4) increase in reliable transportation for the elderly population. To move research to action, it is necessary to engage community members directly and collaboratively in developing these strategies to address health disparities and other structural barriers that rural communities face regarding health and healthcare.